ChemInform Abstract: A New Synthetic Route to Rhenium and Iodine Oxide Fluoride Anions: The Reaction Between Oxoanions and Sulfur Tetrafluoride. Issue 29 (July 2015) - Goettel, James T.; Turnbull, Douglas; Gerken, Michael
Abstract One‐step preparation of [Ag(MeCN)x][ReVIIO2F4] (x = 0, 2, 4) is achieved by addition of excess SF4 to a frozen MeCN solution of Ag[ReO4] at ‐196 °C followed by warming up to room temp.